Effect of Different Hinge Angles on Control Performance Metrics and Disturbance Rejection in Swashplateless Micro Aerial Robots - Karasahin, Ali Tahir (International Journal of Robotics and Control Systems, 2025)
Micro Aerial Robots (MARs) have demonstrated outstanding performance in autonomous applications, making the performance of their controllers critical. The development of controllers for aerial robots using alternative designs rather than standard ones requires that their performance be investigated using different approaches prior to flight. Hence, this paper presents a 2-degree-of-freedom (DOF) test platform designed to evaluate both controller performance and the swashplateless mechanism that generates orientation and position changes. Recent studies have indicated a need to determine the relationship between the hinge angle and controller performance in the context of swashplateless mechanisms. This paper found that the different hinge angles and controller performance relationships on the 2-DOF test platform are investigated through reference tracking and wind disturbance tests. The swashplateless mechanism with a hinge angle of 30◦ showed better performance in terms of control sensitivity and wind disturbance rejection compared to 45◦ and 60◦ hinge angles. Disturbance rejection performance has been tested at a wind speed of 3.3 m/s simulating moderate outdoor wind conditions. The results show that different hinge angles affect controller performance in terms of rise and settling time, overshoot and integral of time absolute of error (ITAE). It has been shown that the choice of hinge angle in the swashplateless mechanism should be such to improve flight performance according to specific application and performance requirements. In addition to advancing the design and control of MARs, these results are expected to contribute to improvements in potential application areas of aerial robots, such as inspection and sensing.